Administration of sales tax - Sharma, Radhey Shyam (New Delhi : Atlantic Publishers & Distributors, 1988)
On the working of sales tax departments of Rajasthan, Uttar Pradesh, Haryana, and Punjab.
Revision of the author's thesis (Ph. D.--University of Rajasthan, Jaipur)
Bibliography: p. [232]-239.
Keywords: Sales tax -- India